Generic orphan drug substitution: a critical analysis of global practices and Saudi Arabia’s perspective - Alakeel, Yousif S.; Rampakakis, Emmanouil; AlRumaih, Ali; AlRuwaisan, Rana; Abushal, Maha; AlDalaan, Abdullah M.; Idrees, Majdy M.; Alanazi, Zaid D.; AlKoait, Hanouf; Muaadi, Abdulrahman; AlAfra, Majed Ali M.; AlShaya, Shaya A.; et al. (Frontiers in Pharmacology, 2024)
In an era of cost pressure, substituting generic drugs represents one of the main cost-containment strategies of healthcare systems. Despite the obvious financial benefits, substitution may require caution or even be contraindicated. In most jurisdictions, to obtain approval, the bioequivalence of generic products with the brand-name equivalent needs to be shown via bioavailability studies in healthy subjects. Rare diseases, defined as medical conditions with a low prevalence, are a group of heterogenous diseases that are typically severe, disabling, progressive, degenerative, and life-threatening or chronically debilitating, and disproportionally affect the very young and elderly. Despite these unique features of rare diseases, generic bioequivalence studies are typically carried out with single doses and exclude children or the elderly. Furthermore, the excipients and manufacturing processes for generic/biosimilar products can differ from the brand products which may affect the shelf-life of the product, its appearance, smell, taste, bioavailability, safety and potency. This may result in approval of generics/biosimilars which are not bioequivalent/comparable in their target population or that meet bioequivalence but not therapeutic equivalence criteria. Another concern relates to the interchangeability of generics and biosimilars which cannot be guaranteed due to the phenomenon of biocreep. This review summarizes potential concerns with generic substitution of orphan drugs and discusses potentially problematic cases including narrow therapeutic index drugs or critical conditions where therapeutic failure could lead to serious complications or even death. Finally, we put forward the need for refining regulatory frameworks, with emphasis on Saudi Arabia, for generic substitution and recent efforts toward this direction.